Pengaruh Brand Familiarity terhadap Brand Credibility Produk Minuman Kemasan - Andi Muhammad Daffa Khalifah R.H; Didin Hikmah Perkasa (Jurnal Ragam Pengabdian, 2026)
The purpose of this study is to investigate how brand familiarity affects brand credibility. This study is essential for comprehending the psychological aspects of consumers that underlie shifts in brand preferences in the packaged tea sector as well as for elucidating the dynamics of customer perception, which are not entirely captured by market share exclusively. Using quantitative research methods, 100 respondents were recruited. Primary data served as the data source. Purposive sampling was the sampling technique. The respondents were men and women aged 17-50, residing in Greater Jakarta (Jabodetabek), and having purchased Teh Pucuk Harum brand products. Partial Least Squares (PLS) was the analysis technique used in this study, using the SmartPLS version 4 analysis tool. A Likert scale was used to measure respondents' responses, ranging from 1-5. This study was conducted in March 2026. The results indicate that brand credibility has a positive and significant influence on brand familiarity. This research also enriches research in the context of fast-moving consumer goods (FMCG), particularly ready-to-drink beverages, which have traditionally been considered low-involvement products. These results indicate that even under conditions of low involvement, credibility still plays a significant role in shaping familiarity.